EMPLOYEES’ INNOVATION ON HOSPITALITY INDUSTRIES AS REVIEWED FROM THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND LEARNING ORGANIZATION - Yoel Wibowo; Yonathan Palumian; Vido Iskandar (Institute of Research and Community Outreach - Petra Christian University, 2023)
Sudden disruption caused by Covid-19 and VUCA business environment has been a wake-up call for business organizations to change, adapt, and transform. Hospitality business organizations, as one of the impacted industries, require transformative leaders to create Learning Organization environment, and to set innovative organization members. This research investigates the relation between Transformational Leadership, Learning Organization, and Innovative Work Behavior particularly in Hospitality Industries (hotels and restaurants) in Surabaya. This research mainly explores theoretical gap left by the predecessor researches by adopting new scaling used especially to evaluate Transformational Leadership and Learning Organization, and methodological gap by utilizing multivariate data analysis towards the respondents’ groups. This research is designed as a descriptive quantitative study, in which data is collected through questionnaire towards the sample. This study points out that while Transformational Leadership does correlate positively with the creation of Learning Organization, it possesses no significant relationship with the establishment of Innovative Work Behavior among the leaders group. Learning Organization also does not mediate the effects between those two. Operational staff, nevertheless, still significantly and positively affected by relation as pointed out by multivariate data analysis.